Utilizing the writing process approach with English as a second language writers: a case study of five fifth grade ESL Arab students - Alhosani, Najwa M. (Kansas State University, 2009)
This qualitative case study sought to gain deeper understanding of the role the writing process approach played in developing the writing ability of five fifth grade Saudi Arabian students when writing in English as a second language. The study extended for five months in a Midwest elementary school serving a large ESL population. Participants of this study included four ESL teachers and five Saudi ESL students, four females and one male. Two main queries guided this study: 1) the roles of ESL teachers when using the writing process approach in teaching writing in English as a second language to five fifth grade Saudi Arabian ESL students; and 2) the role of the writing process approach in the writing development of five fifth grade Saudi Arabian ESL students. The researcher documented data through four sources: classroom observation, interviews with ESL teacher and ESL students, student think-aloud protocols, and student writing samples. The data analysis of the ESL teachers revealed strong advocacy of utilizing the writing process as an effective method to improve ESL Saudi Arabian students’ writing ability. They were successful in employing the writing process approach regardless of their students’ English language proficiency level, using numerous writing strategies including collaborative writing activities, games, varying speed and voice tone, interest in students’ cultures and languages, and social interaction with the students. The data analysis of the study’s student focus revealed that students writing was not a one step process, yet an ongoing cycle in which they prewrite, plan, draft, pause, read, revise, edit, and publish. Students demonstrated different attitudes and behaviors toward writing throughout this study. Four of the students valued their second language (L2); one, however, found English difficult and confusing. Some of the students’ writing sample scores, determined by the Six Traits Writing Rubric, differed by the end of the study while others’ remained the same. This study provided rich data to better understand the importance of teachers utilizing effective writing process techniques and the impact of the writing process approach on Saudi Arabian students learning to write in English in an American school setting.
Keywords: Writing process approach; English as a second language (ESL); Arab elementary students; Elementary teachers; Second language learning; Elementary education; Education, Bilingual and Multicultural (0282); Education, Elementary (0524); Education, Language and Literature (0279)